(untitled) (Journal of the College of Basic Education, 2023)
Expression through drawing is the window through which we look into the depths of the child, as analytical psychological studies of children’s drawings have proven that it is possible, through free drawing that the child does, to reach the incomprehensible part of his behavior and feelings, in addition to the subconscious matters that are not apparent, and to identify his problems. And what he suffers.Thus, drawing is an appropriate tool for dialogue and achieving communication with others alike, even those who are not good at drawing. The symbols produced by the child using a pen or chalk are an expression of what he feels, so some psychologists recommended using drawing with children who are late in school who suffer from poor social and emotional compatibility and who have behavioral problems to identify and solve these problems, in addition to people with special needs who need more. For the artistic expression of ordinary children, as allowing a child with special needs to practice art is to allow him to be an influential member of his environment surrounding him, especially the child who finds it difficult to create a connection between him and others, and suffers from loneliness and closeness to his problems without revealing them, and the researcher specifically means a child Autism, children with autism are a category of special education that needs care, care and attention, as it is a strange world shrouded in mystery, which calls for research and investigation to find out what it is. In general, they are handsome and some of them have special abilities. It is worth noting that the category of autism is constantly increasing, as a number of studies appeared in the past decade that indicated that autism is P at a rate of (4-10) in every 1000, and the number of males predominates over the number of females at a rate of (1.4). (Abu Fakhr, 1988, p. 265). Through the survey conducted by the researcher in the literature in this field, she found many studies that specialized in children’s drawings, some of which were concerned with the characteristics of children’s drawings and their attitudes when expressing, and others examined the characteristics of deaf children’s drawings and other features of drawings of primary school students, while she did not findThe researcher did not study any study that dealt with the characteristics of the drawings of this segment of society, so the researcher decided to study the characteristics of the drawings of children with autism.Based on the foregoing, the problem of the current research is based on answering the following questions:1. Do children with autism have characteristics of artistic expression of their own?2. Do the characteristics of artistic expression of autistic children differ from the characteristics of artistic expression of normal children?